(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Chronic heart failure (CHF) is one of the leading public health problems, as there is a clear trend of an increase in the number of patients with CHF, as well as a high level of hospitalizations with decompensation of the disease and mortality. The article provides a clinical and laboratory assessment of a comprehensive examination of patients with this pathology to develop further medical and preventive measures.